Securing multi-media transmission over mobile communication channels. (1st January 2011) - El-said, Shaimaa A.; Hussein, Khalid F.A.; Fouad, Mohamed M.
Security and privacy issues of the transmitted data have become an important concern in multimedia technology. In this paper, we propose two computationally efficient and secure video in-compression encryption models. Both models use adaptive lossy image compression (ALIC) technique (El-said et al., 2010) for video compression and optimised multiple Huffman tables (OMHT) technique (El-said et al., 2011) for video encryption. We achieve computational efficiency by using the proposed ALIC technique that exploits the frequently occurring patterns in the DCT coefficients of the video data. Computational complexity of the encryption is made proportional to the number of DCT transmitted coefficients in each video frame. The proposed video encryption models produce an encrypted coded sequence with an improved quality for the high compression ratios when compared to the existing techniques. The performances of the proposed models are compared with those of the existing techniques with respect not only to their compression performance but also their security level. The simulation study for the two models over mobile communication system proves that the proposed models perform well in the presence of transmission errors.